PTU-126 High Incidence of Oesophageal Dysmotility and Increased Inspiratory Gastro-Oesophageal Pressure Gradients in Patients with Unexplained Respiratory Symptoms. (17th August 2016) - Burke, JM; Jackson, W; Waudby, PW; Morice, AH
Abstract : Introduction: It has been suggested that reflux and aspiration are common precipitants in respiratory diseases such as cough, asthma and Chronic Obstructive Pulmonary Disease. An excess of acid in these patients has been demonstrated by conventional pH monitoring, but correlation with symptoms are relatively poor. We have previously hypothesised that oesophageal dysmotility leading to both acid and non-acid aspiration may be an important etiological mechanism. Studies have also highlighted the importance of the gastro-oesophageal pressure gradient (GOPG) in the prevalence of reflux. 1 Methods: High Resolution Oesophageal Manometry (HRM) was performed in 121 patients, 61 of whom presented primarily with unexplained respiratory symptom and complained predominantly of chronic cough (50), or breathlessness (11). An age and sex matched control group was chosen from patients presenting with suspected gastro-oesophageal reflux disease (GORD). The HRM findings of 61 patients (38 female), mean age 56 (range 18–81) with respiratory symptoms were compared with those of 60 suspected GORD patients (39 female), mean age 57, (range 19–81). Results: Mean lower oesophageal sphincter (LOS) and upper oesophageal sphincter (UOS) resting pressures were similar between the two groups. There were fewer intact swallows in the respiratory group compared to those of the GORD group (42% vs 57%, P = 0.03). Intraoesophageal pressure was significantly lower during inspiration in the respiratory group compared to those of the GORD group (-11.5mmHg vs -8.7, p = 0.001). Consequently, there was a significantly higher GOPG was found in respiratory patients compared to those of the GORD group (46 mmHg vs 33 mmHg, p < 0.01). Conclusion: Using High Resolution Oesophageal Manometry, we have demonstrated a higher prevalence of oesophageal dysmotility in patients with unexplained respiratory symptoms than those presenting with typical GORD. Moreover, we have shown that those with unexplained respiratory symptoms exhibit higher inspiratory GOPGs and greater LOS peak contractions possibly stimulating an afferent vagal cough response. Reference: 1 Ayazi S, DeMeester SR, et al . Thoracic-abdominal pressure gradients during the phases of respiration contribute to gastroesophageal reflux disease. Digestive Disease and Sciences 2011;56 :1718–22. Disclosure of Interest: None Declared